Family socioeconomic position and changes in planned health care for children with chronic diseases during the COVID-19 pandemic in Italy - Moirano, Giovenale; Pizzi, Costanza; Rusconi, Franca; Maule, Milena; Richiardi, Lorenzo; Popovic, Maja (Frontiers in Public Health, 2023)
Introduction: With the current study we aimed at evaluating whether during the COVID-19 pandemic children affected by chronic diseases were impacted by the deferral of planned health care caused by the restriction measures.Design: We analysed data of the Italian population-based birth cohort NINFEA, which includes children recruited in foetal life between 2005 and 2016. Women who completed the 4-year NINFEA follow-up questionnaire before November 2020 (N = 5307) were invited to complete a questionnaire targeted at evaluating impacts of the pandemic on children health. The questionnaire asked mothers to report whether their children had a chronic disease or condition that required one or more regular health check by a doctor in 2019 (used as reference period) and whether the children had problems in making routine health checks after March 2020.Results: We obtained information on 3721 children. Out of 353 children with a chronic disease that required at least one medical visit in 2019, 130 (36.8%) experienced problems during the pandemic. Lower family income resulted associated with higher risk of experiencing health access problems. We observed that children living in families at lower income tertiles had more chance of experiencing healthcare access problem compared to children living in families at the highest income tertile (Prevalence Rate Ratio for a tertile decrease in family income: 1.22; 95% CIs: 1.02-1.49).Our study underlines that the COVID-19 pandemic may have caused healthcare access problems for children with prevalent chronic diseases, especially among those living in households with a low socioeconomic position.